Targeted surveillance detected novel beaked whale circovirus in ten new host cetacean species across the Pacific basin - Clifton, Cody W.; Silva-Krott, Ilse; Marsik, Michael G.; West, Kristi L. (Frontiers in Marine Science, 2023)
The first cetacean circovirus, beaked whale circovirus (BWCV), was recently reported in a Longman’s beaked whale (Indopacetus pacificus) stranded in Hawai‘i and represents an emergent disease with unknown population impacts. In other species, circovirus infection may cause mortality or opportunistic co-infection by other pathogens. We report on a targeted surveillance of stranded cetaceans in the Pacific basin, including archived beaked whale species, strandings where pathological findings suggested disease presence, mass stranded animals, and additional individuals to represent a broad range of Hawaiian cetacean species. Archived tissues primarily from the brain, kidney, liver, lung, spleen, and lymph nodes of individuals stranded between 2000 and 2020 (n=30) were tested by PCR for the presence of BWCV. Suspect positive tissue amplicons were confirmed as BWCV through sequencing. Of the screened individuals, 15 animals tested positive in one or more tissues, with a single striped dolphin (Stenella coeruleoalba) testing positive in all six tissues. The highest rate of detection among positive cases was found in the brain (69%), followed by lymph (67%) and lung tissues (64%). Additionally, co-infections of cetacean morbillivirus (n=3), Brucella ceti (n=1), and Toxoplasma gondii (n=1) were found among the positive cases. These results expand the potential host range for BWCV into ten additional odontocete species. New host species include a dwarf sperm whale (Kogia sima) that stranded on O‘ahu in 2000, predating the initial case of BWCV. The results broaden the known geographic range of BWCV to Saipan in the Western Pacific, and American Samoa in the South Pacific, where stranded Cuvier’s beaked whales (Ziphius cavirostris) tested positive. Although the clinical significance is currently unknown, this study demonstrates that BWCV has a high prevalence within targeted cetacean screening efforts. Infectious diseases pose a major threat to cetaceans and BWCV may represent an important emerging disease within populations spanning the central, Western, and South Pacific.